RTB Innovation Catalog - Method and Work Plan - Sarfatti, P.; Bonaiuti, Enrico; Sartas, Murat; Schut, Marc; Sotiris, P. (2021)
This document describes the method for building RTB’s Innovation Catalog. We start by defining the objectives of this research, the problems and the challenges we are addressing. Most CGIAR innovations are documented in a way that does not favor their wider use. This has limited the contribution of CGIAR innovations to the developmental challenges that CGIAR investors demand. The goal of this research is to contribute to the CGIAR innovation management system that will enable the deployment of innovations faster, at a larger scale, and a reduced cost, having a more significant impact where they are needed the most. The purpose of the Innovation Catalog is to document RTB innovations, in a way that is easily accessible, and understandable. The Catalog will be user-friendly (see definition in Section 6.2). Technical terms, indicators, and categories will be standardized. The type of language and depth of information will be tailored to different types of users. The RTB Innovation Catalog will be developed using a tailor-made Scaling Readiness framework. Individual RTB innovations are the building blocks of the Innovation Catalog. Contextual information and connection to innovation packages will be documented for a few of the innovations.